The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.jpainsymman.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Psychiatric Illness on Acute Care Utilization at End of Life From Serious Medical Illness

Abstract: Our findings differ from the increased hospital utilization for patients with psychiatric illness in circumstances other than end-of-life care. Path analyses confirmed hypothesized associations between psychiatric illness and increased utilization mediated by severity of illness and care fragmentation but identified more powerful direct effects decreasing hospital use. Further investigation should examine whether this effect represents a disparity in access to preferred care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(90 citation statements)
references
References 32 publications
3
84
0
3
Order By: Relevance
“…45 We found also that *40% of patients with chronic illness died in a hospital, with almost half of hospital deaths occurring outside the UW Medicine system, highlighting the importance of ensuring that advance care planning is transmitted to other healthcare systems. 46 In addition, we found that the decrease in hospital utilization during the last 30 days of life was consistent for patients older and younger than 65 years, while the decrease in ICU utilization in the last 30 days of life was more prominent for patients older than 65 years.…”
Section: Example Of Specific Metrics Across a Multihospital Healthcarmentioning
confidence: 74%
See 1 more Smart Citation
“…45 We found also that *40% of patients with chronic illness died in a hospital, with almost half of hospital deaths occurring outside the UW Medicine system, highlighting the importance of ensuring that advance care planning is transmitted to other healthcare systems. 46 In addition, we found that the decrease in hospital utilization during the last 30 days of life was consistent for patients older and younger than 65 years, while the decrease in ICU utilization in the last 30 days of life was more prominent for patients older than 65 years.…”
Section: Example Of Specific Metrics Across a Multihospital Healthcarmentioning
confidence: 74%
“…42,50 Examining decedents allows a clear focus on the quality of end-of-life care, but this approach creates a second challenge in that it cannot be used to identify individual patients whose care can be improved, since patients have already died. We are working to define other patient populations with unmet palliative care needs, such as those with psychiatric illness 45 or adult congenital heart disease. 51 A third challenge is that of benchmarking quality and the related consequence of adjudicating accountability for low or high quality.…”
Section: Challenges and Lessons Learned From Ehr-based Metricsmentioning
confidence: 99%
“…Annual patient volume exceeded 64,000 hospital admissions and 1.6 million outpatient and emergency department visits. 9,10 …”
Section: Methodsmentioning
confidence: 99%
“…Characteristics of the 23 included studies are presented in Table 1. Fourteen studies reported health care at end of life (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) and 13 studies reported place of death in patients with a serious mental illness (13,28,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) and. Four studies reported both outcomes (28,(34)(35)(36).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…There was great variability in the size of the study sample from which the sample of people with serious mental illness. In two studies (28,32), the whole sample comprised eligible adult subjects with serious mental illness, whom were included in the synthesis of results, whilst other studies presented results for subsamples with serious mental illness from a Most studies were from the USA (13,24,(30)(31)(32)34,35,38) and Canada (29,36,43); the remaining studies were from Denmark (41,42), the UK (28,44), France (39), the Netherlands (25), Australia (27,33), New Zealand (23), Japan (40) and Taiwan (26,37). The mean/median age of subjects ranged between 47 and 79.…”
Section: Study Characteristicsmentioning
confidence: 99%